Volatile anaesthetics added to cardiopulmonary bypass are associated with reduced cardiac troponin. (October 2017) - Bignami, Elena; Guarnieri, Marcello; Pieri, Marina; De Simone, Francesco; Rodriguez, Alcira; Cassarà, Luigi; Lembo, Rosalba; Landoni, Giovanni; Zangrillo, Alberto
Background: Every year, over 1 million cardiac surgical procedures are performed all over the world. Reducing myocardial necrosis could have strong implications in postoperative clinical outcomes. Volatile anaesthetics have cardiac protective properties in the perioperative period of cardiac surgery. However, little data exists on the administration of volatile agents during cardiopulmonary bypass. The aim of this study was to assess if volatile anaesthetics administration during cardiopulmonary bypass reduces cardiac troponin release after cardiac surgery. Materials and methods: We retrospectively analysed data from 942 patients who underwent cardiac surgery in a teaching hospital. The only difference between the groups was the management of anaesthesia during CPB. The volatile group received sevoflurane or desflurane while the control group received a combination of propofol infusion and fentanyl boluses. Patients who received volatile anaesthetics during cardiopulmonary bypass (n=314) were propensity-matched 1:2 with patients who did not receive volatile anaesthetics during CPB (n=628). Results: We found a reduction in peak postoperative troponin I, from 7.8 ng/ml (4.8-13.1) in the non-volatile group to 6.8 ng/ml (3.7-11.8) in the volatile group (p=0.013), with no differences in mortality [2 (0.6%) in the volatile group and 2 (0.3%) in the non-volatile group (p=0.6)]. Conclusions: Adding volatile anaesthetics during cardiopulmonary bypass was associated with reduced peak postoperative troponin levels. Larger studies are required to confirm our data and to assess the effect of volatile agents on survival.